Risk of death in patients with progressive pulmonary sarcoidosis - Bargagli, Elena; Torricelli, Elena; Fusha, Erjona; Cavigli, Edoardo; Moroni, Chiara; Pistolesi, Massimo; Rosi, Elisabetta; Voltolini, Luca (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Not available